Death of Military Working Dogs Due to Bartonella vinsonii Subspecies berkhoffii Genotype III Endocarditis and Myocarditis. Issue 3 (1st March 2017) - Shelnutt, Leslie M.; Balakrishnan, Nandhakumar; DeVanna, Justin; Batey, Kenneth L.; Breitschwerdt, Edward B.
ABSTRACT: Objectives: As a result of extensive field-related activities, military working dogs (MWDs) have an increased occupational risk for acquiring vector-borne infectious diseases. Methods: Indirect fluorescent antibody, Bartonella alpha-proteobacteria growth medium enrichment culture, and 16-23S Bartonella intergenic transcribed spacer polymerase chain reaction were performed using blood, serum, or tissue specimens. Results: Endocarditis was diagnosed in three MWDs infected with Bartonella vinsonii subspecies (subsp.) berkhoffii genotype III. One dog was also infected with Bartonella rochalimae . Conclusions: B. vinsonii subsp. berkhoffii genotype III may represent an occupational risk for MWDs that develop endocarditis or myocarditis. Comprehensive periodic screening for canine vector-borne infections, in particular occult infections caused by Bartonella spp, is prudent to avoid serious or life-threating illnesses.